1975
DOI: 10.1139/y75-056
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolism of 4-Chlorobiphenyl in the Pig

Abstract: 1-Chlorobiphenyl was administered retrocarotidly in a saline oil emulsion to anesthetized pigs. The urine obtained from the pigs 2 h after injection of the 4-chlorobiphenyl was analyzed for metabolites. Mass spectrometric analysis indicated the presence of a monohydroxylated species (M+ 204) and a dihydroxylated compound (M+ 220) and these were identified as 4'-chloro-4-biphenylol and 4'-chloro-3,4-biphenyldiol, respectively. Examination of the urine extracts from pigs 0.5, 1, and 2 h after administration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…40,42,43 These studies have reported that 4′OH-PCB3 > 3′4′-diOH-PCB3 > 3′OH-PCB3 are three major phenolic metabolites in naïve animals. Rats induced with phenobarbital (PB) and 3-methylcholanthrene (3-MC) exhibited enhanced metabolism of PCBs, suggesting a role for hepatic CYP1A and 2B isoforms in the formation of phenolic metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…40,42,43 These studies have reported that 4′OH-PCB3 > 3′4′-diOH-PCB3 > 3′OH-PCB3 are three major phenolic metabolites in naïve animals. Rats induced with phenobarbital (PB) and 3-methylcholanthrene (3-MC) exhibited enhanced metabolism of PCBs, suggesting a role for hepatic CYP1A and 2B isoforms in the formation of phenolic metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the formation of arene oxide intermediates in PCB metabolism was first provided by Gardner et al (103) in their study of the metabolism of 2,5,2',5'-tetrachlorobiphenyl and in a later study of 4-chlorobiphenyl metabolism by Safe et al (96), which was specifically designed to provide evidence of an arene oxide intermediate. Metabolism of PCBs which do not have two adjacent unsubstituted carbon atoms by hepatic mixed-function oxidases, via direct hydroxylation of the biphenyl molecule and/or the formation of an arene oxide between a chlorinated and an unsubstituted carbon atom could occur, but each of these mechanisms would be expected to be slower than arene oxide formation between two unsubstituted carbon atoms (104,105).…”
Section: Metabolism Of Individual Pcbsmentioning
confidence: 99%
“…Environmental Health Perspectives (43), especially in cases where vicinal (1,2 or adjacent) unsubstituted carbons are found in the molecule (44). The corresponding dihydrodiol and/or catechol generally occur along with the phenolic metabolites.…”
Section: Nonmetabolic Alteration Of Chlorinated Biphenylsmentioning
confidence: 99%